Quinine Treatment Selects the pfnhe-1 ms4760-1 Polymorphism in Malian Patients with Falciparum Malaria - Kone, Aminatou (2013)
Background. The mechanism of Plasmodium falciparum resistance to quinine is not known. In vitro quantitative trait loci mapping suggests involvement of a predicted P. falciparum sodium-hydrogen exchanger (pfnhe-1) on chromosome 13. Methods. We conducted prospective quinine efficacy studies in 2 villages, Kolle and Faladie, Mali. Cases of clinical malaria requiring intravenous therapy were treated with standard doses of quinine and followed for 28 days. Treatment outcomes were classified using modified World Health Organization protocols. Molecular markers of parasite polymorphisms were used to distinguish recrudescent parasites from new infections. The prevalence of pfnhe-1 ms4760-1 among parasites before versus after quinine treatment was determined by direct sequencing. Results. Overall, 163 patients were enrolled and successfully followed. Without molecular correction, the mean adequate clinical and parasitological response (ACPR) was 50.3% (n = 163). After polymerase chain reaction correction to account for new infections, the corrected ACPR was 100%. The prevalence of ms4760-1 increased significantly, from 26.2% (n = 107) before quinine treatment to 46.3% (n = 54) after therapy (P = .01). In a control sulfadoxine-pyrimethamine study, the prevalence of ms4760-1 was similar before and after treatment. Conclusions. This study supports a role for pfnhe-1 in decreased susceptibility of P. falciparum to quinine in the field.